The Relationship Between Behavioral Inhibition and Behavioral Activation Systems, Impulsiveness, and Internet Gaming Disorder Among Students of Different Ages - Xiang, Hui; Tian, Xiaolin; Zhou, Yu; Chen, Jieyu; Potenza, Marc N.; Zhang, Qun (Frontiers in Psychiatry, 2021)
Background and Aims: Internet Gaming Disorder (IGD),which is an underlying symptom classified as a behavioral addiction disorder, has many related social problems that have garnered the bulk of attention in recent research. However, its psychological/behavioral mechanism is still unclear. The purpose of the current study was to explore the relationship between IGD and impulsivity which is regulated by behavioral inhibition and activation among different age groups. Methods: A total of 1525 students completed Young's Internet Addiction Test(IAT),Online Game Addiction Questionnaire, the Behavioral Inhibition System/Behavioral Activation System(BIS/BAS) scales and the Barratt Impulsiveness Scale-11(BIS-11). Results:1)The prevalence of IGD in different ages students was 10.3%. 2)BIS, BAS-Fun seeking (BAS-F), and BIS-11scores indicated that there were significant differences between IGD and non-IGD individuals.3) BIS showed significant differences in different grades(i.e., between undergraduates and middle school students with IGD;F = 3.10, p< 0.05). 4) The IAT scores demonstrated a significant positive correlation with BIS scores (r = 0.375, p<0.05) among undergraduates with IGD; IAT scores of high school students with IGD were negatively correlated with BAS-Reward (BAS-R) (r = -0.28, p<0.05).5)BIS and BIS-11 together could explain 14.9% variance of IGD among the college group; BAS-R and BAS-F together could explain 16.7% variance of IGD among the high school group(p<0.05) . Conclusions: The relationships between IGD and BIS, BAS-F, BAS-D, BIS-11 scores differed due to the age group of individuals tested.